Paracelsus (Theophrastus Bombastus von Hohenheim, 1493-1541) : essential theoretical writings - Paracelsus, 1493-1541. (Aries Book Series, 2008)
The daunting writings of Paracelsus-the second largest 16th-century body of writings in German after Luther's-contributed to medicine, natural science, alchemy, philosophy, theology, and esoteric tradition. This volume provides a critical edition of essential writings from the authoritative 1589 Huser Paracelsus alongside new English translations and commentary on the sources and context of the full corpus. The Essential Theoretical Writings incorporate topics ranging from metaphyics, cosmology, faith, religious conflict, magic, gender, and education, to the processes of nature, disease and medication, female and male sufferings, and cures of body and soul. Properly contextualized, these treatises yield rich extracts of Renaissance and Reformation culture, soundings of 16th-century life, and keys to an influential but poorly understood early modern intellectual tradition.